2013
DOI: 10.1021/ie400855b
|View full text |Cite
|
Sign up to set email alerts
|

Removal of Chemical Oxygen Demand and Color from Simulated Textile Wastewater Using a Combination of Chemical/Physicochemical Processes

Abstract:  Large quantities of dyes used in the textile industry are lost to the effluents and flows into surface water during the manufacturing and processing operations. Many methods have been used such as biological, physical and chemical treatment of dye containing wastewater. Among these treatment technique, activated sludge, flocculation, and adsorption are the most commonly applied methods in Indonesia. Dyes are usually resistant to aerobic degradation, for example decolorization of azo dyes has been found to be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
23
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(23 citation statements)
references
References 28 publications
0
23
0
Order By: Relevance
“…Organic dyes, which are extensively used in industries such as textile, leather, paint, printing inks, plastics, food, drugs and cosmetics, are released into water bodies, resulting in high Chemical Oxygen Demand (COD) even after being treated1. Among these, textile industries release the highest amount of non-biodegradable dye effluents into the environment.…”
mentioning
confidence: 99%
“…Organic dyes, which are extensively used in industries such as textile, leather, paint, printing inks, plastics, food, drugs and cosmetics, are released into water bodies, resulting in high Chemical Oxygen Demand (COD) even after being treated1. Among these, textile industries release the highest amount of non-biodegradable dye effluents into the environment.…”
mentioning
confidence: 99%
“…It uses strong chemical agent to degrade both the organic as well as inorganic matter present in the water samples. The organic matter such as humic acid was also included [27,28], and these results also indicated that the organic matter in raw water had significant effects on residual Al.…”
Section: Relationship Between the Residual Al And The Cod Of Raw Watermentioning
confidence: 74%
“…[1][2][3] Residual dye content from effluents of the textile dyeing and finishing industry results in major environmental concerns in current days which are associated with the intensity of color and organic properties such as chemical oxygen demand (COD). [4][5] Most dyestuffs are highly resistant to microorganisms and recalcitrant to conventional biological wastewater treatment processes having aromatic structures. [6][7] Unfortunately, conventional wastewater treatment of textile industries that couples chemical coagulation with activated sludge processes cannot satisfy the more restrictive criteria for color.…”
Section: Introductionmentioning
confidence: 99%